Respuesta :

In this sequence, our common ratio is -3 (each value is -3 times the previous value). The first (or 1th) term of the sequence is 6, so we can form our equation:

[tex]y=6(-3)^(^x^-^1^)[/tex]

Now we have to find the 11 term. To do so, we plug 11 into our equation where the x would be. Once that's done, we do the math as follows:

[tex]y=6(-3)^(^1^1^-^1^)[/tex] (plug in)

[tex]y=6(-3)^(^1^0^)[/tex] (simplify by subtracting 1 from 11 to get 10)

[tex]y=6(59049)[/tex] (simplify by calculating 3 to the power of 10 to get 59049)

[tex]y=354294[/tex] (solve by multiplying 6 by 59040 to get 354294

Therefore, our 11th term in the sequence is 354394.